Constructive alignment in foreign language curricula: an exploration of teaching and assessment practices in Dutch secondary education. Issue 3 (4th May 2023) - Rouffet, Charline; van Beuningen, Catherine; de Graaff, Rick
ABSTRACT: While Communicative Language Teaching (CLT) is recognised as an effective approach worldwide, its implementation in foreign language (FL) classrooms remains difficult. Earlier studies have identified factors impeding CLT implementation, such as a lack of communicative lesson materials or teachers' more traditional views on language learning. In the Netherlands, CLT goals have been formulated at the national level, but are not always reflected in daily FL teaching and assessment practice. As constructive alignment between learning goals, classroom activities and assessments is a precondition for effective teaching, it is important to gain a deeper understanding of the degree of alignment in Dutch FL curricula and the factors influencing it. The current study therefore aims to take a systematic inventory of classroom practices regarding the translation of national CLT goals into learning activities and assessments. Findings revealed that teaching activities and classroom assessments predominantly focused on grammar knowledge and vocabulary out of context and, to a lesser extent, on reading skills. External factors, such as teaching and testing materials available, and conceptual factors, such as teachers' conceptions of language learning, were identified to contribute to the observed lack of alignment. Assessments in particular seem to exert a negative washback effect on CLT implementation.